Coexistence and sequence of occurrence of other allergic diseases in children with atopic dermatitis - Wanat-Krzak, Małgorzata; Kapińska-Mrowiecka, Monika; Kurzawa, Ryszard (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2003)
The paper evaluates the prevalence and sequence of occurrence of other allergic diseases in 257 children with atopic dermatitis who were treated in 1995-97 in the Allergic Diseases Department of Institute of Tuberculosis and Lung Diseases in Rabka. The most common was coexistence of atopic dermatitis and asthma (86%). Data from family history, and skin prick tests with food and airborne allergens and also specific IgE taking into account the prevalence in the group of preschool children and the group of school children were analyzed.